Assessment The Role of Schools in Promoting Public Health Practices in Governmental Schools- Gaza Strip - Hawajri, Ahmed Mohammed; Nassar, Abdallah Naser; Nimer, Mohammed Jebreldar Abuanja (Journal of medical and pharmaceutical sciences, 2021)
This study aimed to Assessment the role of schools in promoting public health practices in governmental schools- Gaza strip. This cross- sectional study method was used a methodological triangulation provided a combination between quantitative (self- administrated questionnaire) and qualitative paradigms (focus groups discussion with students and caregivers). The study sample was 170- school health coordinator, from governmental schools, located in directorates of education in North Gaza, West Gaza, Middle area, Khanyounes, and Rafah. Data shows the roles of schools in promoting public health practices. Most of study sample was agree that, there is a role for schools in promoting public health practices in the fourth school health axes. The relative weight of the total axes was 78.90%, and the mean equal 3.94. While the sub- areas was axis, (Nutrition) occupied the first rank with a relative weight reached 81.36%, and the mean equal 4.07. The axis (Hygiene) occupied the second rank with relative weight 79.54%, and the mean equal 3.98. The axis (Health Education) occupied the third rank with relative weight 77.87%, and the mean equal 3.89. The axis (Environment) occupied the last rank with relative weight 77.37%, and the mean equal 3.87. A statistically significance relationship was found between the role of schools in promoting public health practices and gender; there are significant differences in favor of females schools. Moreover the results demonstrated that there is a statistically significance relationship was found between the role of schools in promoting public health practices and the directorate of education; there are significant differences in favor of directorate of education in west Gaza. Study findings highlight the need for more attention in the cleanliness and continuous maintenance of bathrooms in schools, and the study recommended that students needs a food program in school. In addition, environmental clubs in schools should be more activation. Moreover, MEHE should be more attention in training SHC, especially about promoting public health practices. Finally, schools need more health education meetings for students and caregivers.